Current Status of Use of Biological Medicines on Rheumatoid Arthritis Patients in the Musculoskeletal and the Rheumatoid Department in E Hospital in 2023 - Thi Xuan, Bui; Van Thuy, Ha; Thi Thu Thu, Tran; Thi Thu Huong, Vu (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 41 No 2, 2025)
To describe the current status of biological drug use in patients with rheumatoid arthritis at E Hospital in 2023. Research method: A retrospective cross-sectional description of medical record data and payment slips of patients diagnosed with rheumatoid arthritis. Included in the study were patients who were prescribed biological drugs for inpatient treatment at the department of Musculoskeletal and Rheumatology, E Hospital, from January 2023 to December 2023. Results: The study was conducted on a total of 89 medical records of 23 rheumatoid arthritis patients with an average age of 57, with a female majority (87%). The hands were the most affected joints by rheumatoid arthritis among the above group at 28.1%. In 2023, the Department of Rheumatology at E Hospital used four biological drugs: adalimumab (Humira), golimumab (Simponi), infliximab (Remicade), and tocilizumab (Actemra), of which adalimumab (Humira) was the most frequently described (47.2%). Most patients treated with biologic drugs had a short hospital stay of 1 to 5 days (73%). Patients were hospitalized for treatment in cycles of medication, and medication changes were observed in 6 patients (26%). The cost of infliximab (Remicade) was the most expensive of the drugs used at 23,637,600 VND per treatment cycle.